2013
DOI: 10.1590/s0100-69162013000100020
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration and crop coefficient for potato in organic farming

Abstract: The aim of this study was to quantify the water consumption and the crop coefficients (Kc) for the potato (Solanum tuberosum L.), in Seropédica, Rio de Janeiro (RJ), Brazil, under organic management, and to simulate the crop evapotranspiration (ETc) using the Kc obtained in the field and the ones recommended by the Food and Agriculture Organization (FAO). The water consumption was obtained through soil water balance, using TDR probes installed at 0.15m and 0.30m deep. At the different stages of development, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
2
11
0
1
Order By: Relevance
“…According to CARVALHO et al (2013), the climate in the region is classified as Aw (Köppen classification), with high temperatures and rains in summer, and dry weather with mild temperatures in winter. The rains are concentrated in the period Nov-Mar (annual averages for: rainfall: 1213mm; temperature: 24.5°C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to CARVALHO et al (2013), the climate in the region is classified as Aw (Köppen classification), with high temperatures and rains in summer, and dry weather with mild temperatures in winter. The rains are concentrated in the period Nov-Mar (annual averages for: rainfall: 1213mm; temperature: 24.5°C).…”
Section: Methodsmentioning
confidence: 99%
“…Although the water amount applied by irrigation has been enough to raise θ to the field capacity, Dd and ΔSW were also monitored by TDR. The Ep term was determined for each treatment according to the methodology described by CARVALHO et al (2013). It consisted of the fraction of the precipitated depth that contributed to raise the soil moisture to the field capacity in the depth corresponding to the root system.…”
Section: Methodsmentioning
confidence: 99%
“…Sensor calibration was performed based on daily readings of the apparent dielectric constant (ka) and respective determination of soil moisture by the gravimetric model. According to CARVALHO et al (2013), soil samples were collected in calibration bowls built in representative locations of both textural classes, where sensors with 0.15 m length metal rods were horizontally installed at 0.2 and 0.4 m depth. From the volumetric moisture (θ) and kA data, the following adjustment equations were obtained via simple regression analysis: θ 20 = 0.0099 ka + 0.1048 and θ 40 = 0.011 ka + 0.103 (for B1), and θ 20 = 0.0132 ka + 0.0213 and θ 40 = 0.0108 ka + 0.0401 (for B2).…”
Section: Methodsmentioning
confidence: 99%
“…8 and was done by following averaging method (Biswas et al, 2014). Carvalho et al (2013) found the Kc values of 0.35, 0.45, 1.29 and 0.63 for initial, development, mid-season and late season, respectively in Rio de Janeiro (RJ), Brazil. Kashyap and Panda (2001) found the Kc values of potato at initial, crop development, reproductive and maturity were 0.42, 0.85, 1.27 and 0.57, respectively at the experimental farm of the Agricultural and Food Engineering Department, Indian Institute of Technology, Kharagpur, India.…”
Section: Determination Of Crop Coefficientmentioning
confidence: 98%
“…Tyagi et al (2000) recommended utmost importance for the locally calibrated Kc values for a given climatic condition. Many researchers determined Kc values of potato using different lysimeter under various climatic conditions across the world (Carvalho et al, 2013;Kashyap and Panda, 2001;Allen et al,. 1998;Ferdous et al, 1985;Hane and Pumphre, 1984;Doorenbos and Kassam, 1979;Doorenbos and Pruitt, 1977).…”
Section: Introductionmentioning
confidence: 99%